Endothelin‐1 increases the expression of VEGF‐R1/Flt‐1 receptors in rat cultured astrocytes through ETB receptors. (8th July 2014) - Koyama, Yutaka; Hayashi, Mio; Nagae, Ryuji; Tokuyama, Shogo; Konishi, Tomohiro
Abstract Expressions of vascular endothelial growth factor (VEGF) receptors in astrocytes are increased in damaged brains. To clarify the regulatory mechanisms of VEGF receptors, the effects of endothelin‐1 (ET‐1) were examined in rat cultured astrocytes. Expressions of VEGF‐R1 and ‐R2 receptor mRNA were at similar levels, whereas the mRNA expressions of VEGF‐R3 and Tie‐2, a receptor for angiopoietins, were lower. Placenta growth factor, a selective agonist of the VEGF‐R1 receptor, induced phosphorylation of focal adhesion kinase (FAK) and extracellular signal regulated kinase 1/2 (ERK1/2). Phosphorylations of FAK and ERK 1/2 were also stimulated by VEGF‐E, a selective VEGF‐R2 agonist. Increased phosphorylations of FAK and ERK1/2 by VEGF165 were reduced by selective antagonists for VEGF‐R1 and ‐R2. Treatment with ET‐1 increased VEGF‐R1 mRNA and protein levels. The effects of ET‐1 on VEGF‐R1 mRNA were mimicked by Ala1, 3, 11, 15‐ET‐1, a selective agonist for ETB receptors, and inhibited by BQ788, an ETB antagonist. ET‐1 did not affect the mRNA levels of VEGF‐R2, ‐R3, and Tie‐2. Pre‐treatment with ET‐1 potentiated the effects of placenta growth factor on phosphorylations of FAK and ERK1/2. These findings suggest that ET‐1 induces up‐regulation of VEGF‐R1 receptors in astrocytes, and potentiates VEGF signals in damaged nerve tissues. <boxed-text content-type="graphic" id="jnc12770-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> To clarify the regulatory mechanisms of vascular endothelial growth factor (VEGF) receptors, the effects of endothelin‐1 (ET‐1) were examined in rat cultured astrocytes. Effects of selective VEGF‐R1 and R2 agonist showed that these receptors were linked to focal adhesion kinase (FAK) and extracellular signal regulated kinase 1/2 (ERK1/2). Treatment with ET‐1 increased expression of VEGF‐R1, which was mediated by ETB receptors. Pre‐treatment with ET‐1 potentiated the VEGF‐R1‐mediated activations of FAK and ERK1/2. These findings suggest that ET‐1 induces up‐regulation of VEGF‐R1 receptors in astrocytes.